2018
DOI: 10.1111/nph.15080
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key amino acid residues determining product specificity of 2,3‐oxidosqualene cyclase in Oryza species

Abstract: Triterpene synthases, also known as 2,3-oxidosqualene cyclases (OSCs), synthesize diverse triterpene skeletons that form the basis of an array of functionally divergent steroids and triterpenoids. Tetracyclic and pentacyclic triterpene skeletons are synthesized via protosteryl and dammarenyl cations, respectively. The mechanism of conversion between two scaffolds is not well understood. Here, we report a promiscuous OSC from rice (Oryza sativa) (OsOS) that synthesizes a novel pentacyclic triterpene orysatinol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 47 publications
0
40
1
Order By: Relevance
“…They constructed three site‐directed mutants—Y257L, Y257F, and Y257A—and reported that only trace amounts of parkeol were produced through the action of these mutants. No other products were reported . The results reported by them are significantly different from those of our experiments; these differences might be due to a lack of detailed experiments by them.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They constructed three site‐directed mutants—Y257L, Y257F, and Y257A—and reported that only trace amounts of parkeol were produced through the action of these mutants. No other products were reported . The results reported by them are significantly different from those of our experiments; these differences might be due to a lack of detailed experiments by them.…”
Section: Discussioncontrasting
confidence: 99%
“…Xue et al. recently reported mutagenesis experiments targeting the Tyr257 residue of parkeol synthase ( Os PA, Os OSC2) . They constructed three site‐directed mutants—Y257L, Y257F, and Y257A—and reported that only trace amounts of parkeol were produced through the action of these mutants.…”
Section: Discussionmentioning
confidence: 99%
“…4a). This is supported by site-directed mutagenesis work 52 which report the functional conversion of a committed parkeol synthase to a variant producing orysatinol (48). Further support comes from phylogenetic analysis suggesting that the wild type orysatinol synthase shares a common (parkeol (8) producing) ancestor with the committed parkeol synthase.…”
Section: Breaking the Protosteryl/ Dammarenyl Dichotomymentioning
confidence: 87%
“…The mechanistic diversity of OSCs remains intriguing. Although many attempts have been made to study the underlying mechanism (Hart et al ., ; Herrera et al ., ; Tetsuo Kushiro et al ., ; Liu et al ., ; Salmon et al ., ; Xue et al ., ), the mechanism of conversion between scaffolds remains poorly understood. Sequence analysis has shown that all three Tw OSCs contained terpenoid cyclase/protein prenyltransferase alpha–alpha toroid domains, but only Tw OSC2 contained conserved sites of terpene synthase that are rich in aromatic residues, in the C‐terminal region.…”
Section: Discussionmentioning
confidence: 99%